SOCIO-ECONOMICS AND LIVESTOCK GRAZING PATTERN IN AND AROUND GREY GORAL HABITAT IN MACHIARA NATIONAL PARK, AZAD JAMMU AND KASHMIR - M. Anwar; N. Ashraf; N. Shafi; M. S. Awan; M. Sarwar (Journal of Animal and Plant Sciences, 2019)
Grey goral (Naemorhedus goral) is classified asNear Threatened by IUCN Red List. This subspecies is threatened primarily by illegal hunting and competition with livestock, resulting in small and fragmented populations in its current distribution range in Pakistan. Present study documented socio-economic structure of residents and livestock grazing pattern in and around Grey goral habitat at two locations i.e. Machiara and Serli Sacha in Machiara National Park (MNP), Azad Jammu and Kashmir, Pakistan. Socio-economic of people was assessed by questionnaire survey and livestock population in Grey goral habitat was assessed through field sampling as well as questionnaire survey. Average family size was less at Machiara (5.46) than Serli Sacha (6.48). Self-employment (84 %), government employment (16 %) and daily wages labour were identified as major economic activities in the study area. At Serli Sacha, larger proportion of inhabitants (87%) were self- employed than Machiara (84%). At Machiara, 16% of respondents were government employees while there was none in Sarli Sacha. At Machiara, 32 families owned 545 livestock heads with an average of 17 animals per family while at Serli Sacha, 47 families owned 899 livestock heads with an average of 19 animals per family around Grey goral habitat. There was a significant negative correlation between number of Grey goral observed and livestock heads both at Machiara (r= -0.388, p < 0.05, n = 7) and Serli Sacha (r= -0.75, p < 0.05, n = 9). Our study suggests that a comprehensive livestock grazing strategy needs to be developed for protection and conservation of Grey goral and its habitat in MNP.
Keywords: livestock grazing; grey goral; socio-economic survey; livelihood; conservation